LITERATURE IS A SOURCE THAT REVEALS THE TRUTH OF LIFE - Tuychieva Zulaykho Khamrokulovna (Scholar Express Journal, 2022)
In this author tried to give detailed analyses of the works done by different writers comparing their cultural derivation. She took three different writers from various nations and explored world of literature. She also pointed that there is a connection between these both in style and idea. She gave the plot of the story by Katherine Mansfield by citing her fair evaluation. And this helped the reader to follow the author. According to her all three writers in their stories tried to be implicit and did not give a conclusion, instead they forced the reader to figure out the conclusion themselves.
Keywords: World; nations; literature; specificity